The Influence of Accounting Information System Quality, User Trust, and Service Quality on The Decision To Use The Ovo Application in Surabaya - Rizqi Setyo Laksono; Sutrisno T (PT. Maju Malaqbi Makkarana, 2026)
The expansion of digital financial services has contributed to the increasing adoption of digital wallet applications such as OVO in community transaction activities. In this context, the decision to use an application is determined not simply through system-related technical aspects, alongside psychological and operational considerations. This research focuses on examining the influence of the accounting information system quality, user trust, and service quality on the decision to use the OVO application in Surabaya City. Primary data were used in this study, which employed a quantitative approach. Purposive sampling was applied to obtain 100 respondents. The data were gathered through online questionnaires distributed via Google Forms to OVO users in Surabaya City and then analyzed using SPSS Statistics 26. This study involved respondents who were users of the OVO e-wallet in Surabaya City. The results demonstrate that the quality of the accounting information system, user trust, and service quality contribute positively to the decision to use the OVO application in Surabaya City. The use decision regarding the OVO application in Surabaya City is driven by the interplay of sound system quality, strong user trust, and sufficient service quality.